Satellite-derived Alaskan ice-dammed lake drainage events (1985 - 2020) - Brianna Rick; Daniel McGrath (Hydroshare)
Ice-dammed lakes impounded behind glacier dams can undergo multiple fill-and-drain cycles, and rapid drainage can produce damaging floods with significant societal and ecological impacts. Using multitemporal satellite imagery (Landsat and Sentinel-2), we documented 1150 drainage events from 106 ice-dammed lakes over 1985–2020, with an average of 66 events per year over 2015–2020. This dataset provides each ice-dammed lake's location (latitude, longitude), and the image dates before and after a lake drainage event was observed.